2015
DOI: 10.4081/bam.2015.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Persistent muscle fiber regeneration in long term denervation. Past, present, future

Abstract: Despite the ravages of long term denervation there is structural and ultrastructural evidence for survival of muscle fibers in mammals, with some fibers surviving at least ten months in rodents and 3-6 years in humans. Further, in rodents there is evidence that muscle fibers may regenerate even after repeated damage in the absence of the nerve, and that this potential is maintained for several months after denervation. While in animal models permanently denervated muscle sooner or later loses the ability to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In addition to muscle-specific damage, another pathological condition leading to myonuclear misplacement and severe myofiber atrophy is denervation due to spinal cord injury or motor neuron toxicity. Myofibers survive denervation, but they show a typical nuclear misplacement consisting in nuclear clumps followed by stretches of anucleated (and amyofibrillar) sarcoplasm [30,47,48]. Denervation is also characterized by the specific upregulation of several molecular markers, including AchRs and Musk (which are involved in the NMJ) and NCAM and HDAC [46,49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to muscle-specific damage, another pathological condition leading to myonuclear misplacement and severe myofiber atrophy is denervation due to spinal cord injury or motor neuron toxicity. Myofibers survive denervation, but they show a typical nuclear misplacement consisting in nuclear clumps followed by stretches of anucleated (and amyofibrillar) sarcoplasm [30,47,48]. Denervation is also characterized by the specific upregulation of several molecular markers, including AchRs and Musk (which are involved in the NMJ) and NCAM and HDAC [46,49].…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of d-MHC+/dystrophin+ myofibers were significantly elevated in the Pre 2nd bout_1w and Post 2nd bout_1w groups. It has been reported that regenerated myofibers are present in denervated muscles [29,30] and that denervation reversibly affects the domains of the membrane systems involved in excitation-contraction coupling [44]. Fast-velocity ECC (180˚/s) induces functional and structural damage to nerves [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcium uptake during contractions is higher in fast-twitch myofibers than in slow-twitch myofibers [25], and fast-twitch fibers are more susceptible to ECC-induced muscle injury than slow-twitch fibers [26]. Myofiber regeneration can be evaluated using developmental myosin heavy chain (d-MHC) as an indicator, and d-MHC reactivity has been used to assess myofibers after ECC-induced muscle injury [27,28], and in denervated muscles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main purpose of these studies was neuronal replacement, and it remains difficult to use the abovementioned cells to replace autologous neurons in clinical practice. Because the distal nerve stump may be less tolerating than muscle, a more practical strategy to improve regeneration is to maintain the distal nerve in an “available” state to accept the proximal axons [17]. A previous study used mesenchymal stem cell transplantation to activate denervated SCs in predegenerated nerves, but because the denervation time of the distal stump is short, the true utility of this approach is uncertain [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sulaiman and Gordon confirmed that this time window was 6 months in rats [15]. In contrast, recent research believed that even if a rat has been denervated for more than 1 year, the muscle still has the ability to regenerate, which corresponds to better tolerance than nerves [16, 17]. Therefore, this study is aimed at determining the effect of transplanted embryonic neurons on SCs in distal nerve stumps in a rat peripheral nerve injury (PNI) model.…”
Section: Introductionmentioning
confidence: 99%